Efektivitas Realitas Virtual sebagai Alternatif Terapi Keseimbangan Postur Tubuh Pasien Stroke Kronis - Ika Monita; Sandy Faisal (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. Virtual reality is a technology that allows users to interact with an environment that only exists in imagination, but looks like real to the person who uses it. The right time to do virtual reality therapy is 6 months after stroke, which is a chronic phase or it can be a subacute phase but has already experienced stabilization. The purpose of this study was to analyze the effectiveness of virtual reality therapy in chronic stroke patients, and to compare the effectiveness of virtual reality in the experimental group and the control group. The study was conducted using the scoping review method, by searching for articles from the PubMed database with the keywords (